1996
DOI: 10.1046/j.1464-410x.1996.00079.x
|View full text |Cite
|
Sign up to set email alerts
|

The proportional decrease in prostate specific antigen level best predicts the duration of survival after hormonal therapy in patients with metastatic carcinoma of the prostate

Abstract: Objective To examine the usefulness of a test for prostate specific antigen (PSA) to predict survival in hormonally treated patients with metastatic prostate cancer. Patients and methods The study comprised 49 patients (mean age 72 years, sd 6) who underwent orchidectomy for metastatic prostate cancer. PSA was measured before orchidectomy and after 6 months, and the absolute, differential and proportional decreases calculated. A Cox proportional hazards regression model, which controlled for patient age, tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…For example, after prostatectomy PSA levels should remain undetectable. While it remains a matter of controversy whether the PSA level prior to hormonal therapy has any prognostic significance [6][7][8], several preliminary studies have suggested that the percentage and velocity in decline of the PSA levels after hormonal therapy is associated with survival [9][10][11]. To evaluate the proportion of primary hormoneinsensitive, poor-prognosis prostate cancers and to estimate the prognostic significance of PSA decline after hormonal therapy, we retrospectively analysed the clinicopathological characteristics of 236 consecutive endocrinetreated prostate carcinomas diagnosed at Tampere University Hospital (TAUH).…”
Section: Introductionmentioning
confidence: 99%
“…For example, after prostatectomy PSA levels should remain undetectable. While it remains a matter of controversy whether the PSA level prior to hormonal therapy has any prognostic significance [6][7][8], several preliminary studies have suggested that the percentage and velocity in decline of the PSA levels after hormonal therapy is associated with survival [9][10][11]. To evaluate the proportion of primary hormoneinsensitive, poor-prognosis prostate cancers and to estimate the prognostic significance of PSA decline after hormonal therapy, we retrospectively analysed the clinicopathological characteristics of 236 consecutive endocrinetreated prostate carcinomas diagnosed at Tampere University Hospital (TAUH).…”
Section: Introductionmentioning
confidence: 99%
“…PSA has been used as a tumour marker for prostatic carcinoma for 10 years. Despite problems of sensitivity, the serum level of PSA is widely accepted to be the most Patients and methods useful tool for the early detection, evaluation and management of prostatic carcinoma [1][2][3]. More recent The cohort study comprised 218 patients with BPE aged 42-89 (mean 71) years and 43 patients with prostate studies have acknowledged that PSA exists in both a free and complexed form in the blood, and this may cancer aged 63-88 (mean 74) years, all of whom underwent elective TURP at Huddinge Hospital between make it possible to improve the diagnostic value of this blood test [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…This is obvious in Figs 2A‐C. We evaluated PSA and bone metastases, and reported that the proportional decrease in PSA level at 6 months is the best determinant of survival in patients with metastatic prostate cancer [1]; it correlated more closely than EOD. Furthermore, EOD has been shown in numerous studies to only correlate with survival when separating Grade 1 from Grade 2–4.…”
mentioning
confidence: 99%